Một số nội dung của hợp đồng thành lập công ty - Cương, Ngô Huy (VNU Journal of Science: Legal Studies; Vol 20 No 1, 2004)
The memorandum of association creates a legal person. The law therefor requires th> memorandum of association state some clauses. But Vietnamese law has many shortcoming to do that. It is emphasized in the articles the capital clause and the name of the company clause. The author simultaneously points out mentioned shortcoming of Vietnamese law 01 this subject.